Cruel Crown - Aveyard, Victoria; Aveyard, Victoria; Aveyard, Victoria (New York, NY HarperTeen, an imprint of HarperCollins Publishers, 2016)
In two prequels to Red Queen, Queen Coriane recounts her courtship with the crown prince, the birth of a new prince, Cal, and the potentially deadly challenges that lay ahead for her in royal life. Meanwhile, Captain Farley exchanges coded transmissions with the resistance--and stumbles upon a connection that may prove to be the key to an attack on the Nortan capital: Mare Barrow.
Steel scars.
Keywords: Princesses -- Fiction; Government, Resistance to -- Fiction; Princesses -- Fiction; Government, Resistance to -- Fiction; Fantasy fiction